2016
DOI: 10.1136/bcr-2016-214937
|View full text |Cite
|
Sign up to set email alerts
|

From suspected Creutzfeldt-Jakob disease to confirmed histoplasma meningitis

Abstract: A 77-year-old man with chronic obstructive lung disease who was on steroids, presented to the hospital after a fall with subacute headaches and ataxia. During the patient's hospital course, his clinical condition deteriorated with myoclonic jerks, fevers and severe encephalopathy. An extensive workup, including EEG, brain MRI and lumbar puncture, revealed possible Creutzfeldt-Jakob disease. Unfortunately, the patient failed to improve and died 12 days after admission. A brain-only autopsy revealed he had acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…We found 1159 studies and included 108 manuscripts published between 1962 and 2022, totaling 298 patients 7–10,12–115 . We excluded 38 articles that could not be retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…We found 1159 studies and included 108 manuscripts published between 1962 and 2022, totaling 298 patients 7–10,12–115 . We excluded 38 articles that could not be retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…The same analysis with NM and human proteins revealed a strong biological interaction (P-value 1.0e-16) between NM PI protein and human proteins related to prion diseases, axon development, tryptophan metabolism, SLE and blood brain barrier formation. Clinical reports have been found that patients with SLE and prion diseases are more prone to Meningitis (Al Mahmeed et al 2020;Batra et al 2016).…”
Section: Ppi Study Of Neisseria-human Interactionmentioning
confidence: 99%
“…In many cases of Histoplasma meningitis, an alternative diagnosis is often considered based on physical findings and presentation. In one such case, Creutzfeldt–Jakob disease was initially considered, however, on autopsy, Histoplasma yeast forms were found in parenchymal brain tissue [14].…”
Section: Clinical Presentationmentioning
confidence: 99%